Upaya Penemuan Hukum Oleh Hakim di Peradilan - Afrizal (Al-Mizan, 2017)
Law No. 48 of 2009 Article 10 paragraph (1) of the Judicial Authority determines "that the Court prohibited from refusing to examine, decide upon a case filed with the argument of law does not exist or is less clear, but is obliged to examine and hear." Judge as the main organ Court and as executor of judicial power obligatory for the judge to find the law in a case although legal provisions do not exist or are less obvious. This is the problem in writing what method was used directly in an effort judge huk discovery um Character descriptive analysis. The method of analysis used in the study is a qualitative method. In conducting the legal discovery judge there are several methods of methods of interpretation and legal construction methods / arguments. There is also a newly developed method that may be used as alternative to the discovery of a new law that legal hermeneutics.